The limits of globalization : cases and arguments - Scott, Alan, 1956- (International library of sociology., 1997)
This book examines the concrete manifestations of the globalizing forces operating in the world today. It unpicks the rhetoric of globalization in political analysis, cultural theory and urban and economic sociology.